PENGARUH EDUKASI MEDIA BOOKLET TERHADAP PENGETAHUAN NUTRISI IBU HAMIL DALAM UPAYA PENCEGAHAN STUNTING DI PUSKESMAS SAPTA TARUNA KOTA PEKANBARU TAHUN 2025 - Intan Widya Sari; Rina Yulviana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Pregnant women who experience nutritional deficiencies can have an impact on stunting. Therefore, stunting prevention is necessary, one way of prevention is through education to increase pregnant women's knowledge about nutrition. Education is obtained from various media, one of which is booklets. The purpose of this study was to determine the effect of booklet media education about nutrition for pregnant women on maternal knowledge at the Sapta Taruna Community Health Center in Pekanbaru City. The research design used a Quasi Experiment with a pre-test post-test one group design. The sample used was 60 respondents with a purposive sampling technique. This research tool used a nutritional knowledge questionnaire and booklets. The results showed that before the education, the majority of respondents' knowledge was in the sufficient category with an average value of 13.90 and after the education, the majority of respondents' knowledge was good with an average value of 19.32. The Wilcoxon test obtained a p-value of 0.023 0.05, which indicates that there is an effect of providing health education about nutrition for pregnant women. Booklets can be an educational medium to increase pregnant women's knowledge about nutritional needs during pregnancy. Key_words_ Knowledge, Nutrition for pregnant women, Booklet